Improving Applied Business Administration Students’ Reading Comprehension and Vocabulary Acquisition by Using Quizlet - Hindri Febri Ana Sari; Arthur Reinaldo Tanihatu; Hedyan Putra (ETERNAL (English Teaching Journal), 2026)
This study investigates the integration of Quizlet as a digital tool to enhance English reading comprehension and vocabulary acquisition among second-semester Applied Business Administration students at Politeknik Negeri Ambon. The study addresses the urgent need to support ESP students who often struggle with discipline-specific reading due to limited academic vocabulary and low engagement, particularly in vocational higher education contexts. Using a mixed-methods design, data were collected from 45 students through pre-tests and post-tests, classroom observations, reflective journals, interviews, and Quizlet usage logs. Over eight instructional sessions, students engaged with Business Administration reading texts supported by Quizlet activities, including flashcards, games, and cumulative quizzes. Quantitative data were analyzed using paired-samples t-tests and effect size calculations to examine learning gains, while qualitative data were analyzed thematically to explore patterns of engagement and learner perceptions. The findings revealed significant improvements in vocabulary retention (+22.5) and reading comprehension (+23.2), with strong effect sizes. Weekly accuracy rates increased from 61% to 86%, and student engagement rose markedly, with active participation improving from 55% to 91%. Reflective data indicated a positive shift in students’ attitudes toward reading, from perceiving it as monotonous to viewing it as useful and engaging. These results highlight the pedagogical significance of integrating Quizlet as a supportive tool for fostering vocabulary development, reading comprehension, and learner engagement in ESP instruction.